1999
DOI: 10.1021/ic981342x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Information on the Redox Cycling of Nickel(II/III) Complexes in the Presence of Sulfur Oxides and Oxygen. Correlation with DNA Damage Experiments

Abstract: The reactions of the water-soluble complexes [NiCR](2+) (where CR = 2,12-dimethyl-3,7,11,17-tetraazabicyclo[11.3.1]heptadeca-1(17),2,11,13,15-pentaene) and [NiKGH-CONH(2)](+) (where KGH-CONH(2) = lysylglycylhistidinecarboxamide) with sulfite/O(2) and peroxymonosulfate have been investigated using spectrophotometric and rapid-scan techniques. In most cases, the spectral changes suggest the formation of an intermediate Ni(III) species, followed by decomposition reactions which involve a back-reaction to Ni(II). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 27 publications
1
30
0
2
Order By: Relevance
“…The intercept and constant value of k obs at higher S(IV) concentration (in the case of Ni II G 5 and Ni II G 6 autoxidation) in Figure 3( 36 proposed the formation of Ni III L (SO 4 •-) (L=lysylglycylhistidine carboxiamide), where the SO 4 •-radical may coordinate to Ni III L complex. Green et al 37 considered the formation of reactive dimmer species of Ni(II) and Ni(III)Gly 2 HisGly complexes in the oxidative self-decomposition of Ni(III) complex.…”
Section: Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The intercept and constant value of k obs at higher S(IV) concentration (in the case of Ni II G 5 and Ni II G 6 autoxidation) in Figure 3( 36 proposed the formation of Ni III L (SO 4 •-) (L=lysylglycylhistidine carboxiamide), where the SO 4 •-radical may coordinate to Ni III L complex. Green et al 37 considered the formation of reactive dimmer species of Ni(II) and Ni(III)Gly 2 HisGly complexes in the oxidative self-decomposition of Ni(III) complex.…”
Section: Mechanismmentioning
confidence: 99%
“…The balance of S(IV) and O 2 controls the redox cycling process. 2,3,6,8,18,19,[28][29][30][31][32][33][34][35][36] …”
Section: Mechanismmentioning
confidence: 99%
“…al. 32 Important aspects of Co(II)/Co(III) complex in the presence of oxygen need to be considered as some possible step in the oxidation. Studies 34 with Co(II) peptides (glygly, gly-ala, ala-gly and ala-ala) showed the formation of dimeric complexes with μ-superoxo bridges.…”
Section: Initiation In the Absence Of Added Ni(ii) Or Co(ii)mentioning
confidence: 99%
“…para oxidar os dois complexos de Ni(II). 7 Muller e colaboradores 9 , em estudos de lesões no DNA induzidas pela autoxidação de sulfito catalisada por alguns complexos de Ni(II), discutiram a reatividade dos diferentes radicais. O radical SO 3…”
Section: Mecanismo Da Autoxidação De S(ivunclassified
“…•'-) oxidam biomoléculas, incluindo lipídios, proteínas e DNA [7][8][9] . Alguns íons metálicos de transição têm um papel importante na formação desses radicais, uma vez que catalisam a oxidação de sulfito pelo oxigênio 10,11 .…”
Section: Introductionunclassified